The Effect of Servant Leadership, Job Satisfaction and Organizational Culture on Employee Performance Moderated by Good Governance in Women's Cooperative Institution - Wanta, Derry; Augustine, Yvonne (Technium Sustainability, 2021)
This research aims to examine the effect of servant leadership, job satisfaction and organizational culture on employee performance moderated by good governance in women's cooperative institution. This research is a quantitative study using a purposive sampling method with a total sample of 248 employees or members of 19 credit cooperatives woman in Indonesia (Jakarta, Depok, Bogor, Tangerang and Bekasi-Jabodetabek). The test method that will be used by the author is using Structural Equation Modeling-partial Least Square (SEM-PLS). The results of this research prove that (1) Servant leadership has a negative effect on the performance of Women’s cooperative employees (2) Job satisfaction has no effect on the performance of Women’s cooperative employee (3) Organizational culture did not affects the performance of women's cooperative employees (4) Governance moderates the relationship of Servant Leadership on employee performance (5) Governance moderates the relationship between job satisfaction and employee performance in women's cooperatives (6) Governance moderates the relationship between organizational culture and employee performance in women's cooperatives. The significant finding in this study is that gender play a vital role in running cooperative institution. This research can make a major contribution in making specific servant leadership, job satisfaction, organizational culture and governance variables to employee performance of women’s cooperatives in Jabodetabek area that have not been much researched. Future research can study other variable that after employee performance such as financial performance, work discipline, and personality.